PERENCANAAN STRATEGIS DAN PEMBANGUNAN BERKELANJUTAN - Yenny Dwi Suharyani; Djumarno Djumarno (Jurnal Ilmiah Global Education, 2023)
Strategic planning for organizations and the business world is the answer to all problems in planning for the long term. Where it is expected that leaders have the ability to carry out planning by looking at the problems, constraints and challenges faced by the organization, so that they are expected to be able to make the right strategic decisions according to the needs of the organization. Thus strategic planning is needed in preparing programs that have a concept on sustainable development. So it is necessary to understand what elements are needed for sustainable development, including what factors along with the tools needed to develop in a sustainable manner, both at the national development level, and at the regional development level. This paper is an article review that discusses the forms of strategic planning and sustainable development along with the preparation process and the benefits obtained by Organizations or Businesses.